2022
DOI: 10.1186/s12890-022-01866-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the systemic immune-inflammation index predict the prognosis of EGFR-mutant lung adenocarcinoma patients receiving brain metastasis radiotherapy

Abstract: Background The systemic immune-inflammation index (SII) has recently emerged as a predictor of survival in non-small cell lung cancer patients. There is also tight correlation between radiotherapy and immune status, and brain metastases (BM) radiotherapy is an important treatment in patients with BM from lung adenocarcinoma harboring epidermal growth factor receptor (EGFR) mutations. Hence, this study aimed to present the prognostic value of SII and its dynamic changes during BM radiotherapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The controversy may be related to the cutoff values for the grouping and different study populations. So, analyzing the dynamic changes in SII occurring during the clinical course of sepsis may help better assess the prognosis of patients [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The controversy may be related to the cutoff values for the grouping and different study populations. So, analyzing the dynamic changes in SII occurring during the clinical course of sepsis may help better assess the prognosis of patients [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al conducted a retrospective study to determine the dynamic changes in each patient by evaluating both preoperative and postoperative SII. They confirmed that dynamic changes in SII were independent prognostic factors for patients with lung adenocarcinoma harboring epidermal growth factor receptor mutations treated with brain metastases radiotherapy, with the lowest death rate observed in patients with consistently low SII ( 26 ). Zhou et al found that high postoperative SII and ΔSII (defined as postoperative SII minus preoperative SII) were independent risk factors for postoperative CRC.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, insignificant difference in the survival analysis between the two groups before PSM may be due to uneven clinical features, especially those affected by lung-molGPA. Lung-molGPA reportedly provides a better predictive value, suggesting that lung-molGPA can comprehensively and accurately reflect the prognosis of NSCLC complicated by brain metastases ( 24 , 28 30 ). These also suggest the importance of individualized therapy for craniocerebral radiotherapy ( 12 , 31 33 ).…”
Section: Discussionmentioning
confidence: 97%